1967
DOI: 10.1063/1.1754895
|View full text |Cite
|
Sign up to set email alerts
|

THERMAL SWITCHING OF LASER EMISSION OF Er3+ AT 2.69 μ AND Tm3+ AT 1.86 μ IN MIXED CRYSTALS OF CaF2:ErF3:TmF3

Abstract: Pronounced temperature-dependent transfer of excitation from the Er3+ laser pump levels to lower levels of Er3+ was observed in CaF2:ErF3 single crystals at ErF3 concentrations exceeding 12.5 wt %. Transfer of excitation from Er3+ to Tm3+ occurred when TmF3 was included as a second active constituent of the crystals. Stimulated emission of the 4I11/2 → 4I13/2 transition of Er3+ at 2.69 μ at 298°K resulted independently of Tm3+ and as a consequence of concentration quenching of emission of Er3+ from levels abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Laser oscillation at room temperaure in Er3 ion was first reported in 1967 [6]. In later times the Er3 transitions vere object of intensive studies especially in the Soviet Union.…”
Section: Erbiummentioning
confidence: 97%
“…Laser oscillation at room temperaure in Er3 ion was first reported in 1967 [6]. In later times the Er3 transitions vere object of intensive studies especially in the Soviet Union.…”
Section: Erbiummentioning
confidence: 97%
“…It was found that the fluorescence lifetime of the 4F3/2 level of Nd 3 + is slightly shorter in the chioroapatites . Low-threshold room-temperature Ho operation in multiple sensitized hosts has been reported in Ca2ErsF19 [77] and YAG [78]. Stimulated emission in H0 3 + was first reported in singly doped H0 3 +: CaW04 at 77 K. Observation of energy transfer between Er-Ho [72] led to the first report of efficient CW operation at 77 Kin Ho-doped Y AG.…”
Section: E) the Specific Case Of Nd 3 + Crystal Lasersmentioning
confidence: 98%
“…Er 3 -doped materials make it possible to achieve 3-μm laser sources, which correspond to laser transition from 4 I 11∕2 to 4 I 13∕2 by pumping ground-state ( 4 I 15∕2 ) Er 3 ions to the 4 I 11∕2 level using compact InGaAs laser diodes emitting around 970 nm [3][4][5]. The early research can be dated back to the 1960s, when Robinson and Devor first demonstrated a 2.69-μm stimulated emission in an erbium-doped mixed fluoride crystal [6]. After that, a variety of Er 3 -doped laser materials have been developed based on fluoride and oxide hosts [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The early research can be dated back to the 1960s, when Robinson and Devor first demonstrated a 2.69-μm stimulated emission in an erbium-doped mixed fluoride crystal [6]. After that, a variety of Er 3 -doped laser materials have been developed based on fluoride and oxide hosts [2][3][4][5][6][7][8][9][10]. In recent years, sesquioxides, as desired host materials, have excited rising research interest for high-power laser sources because of their good thermomechanical property [11][12][13].…”
Section: Introductionmentioning
confidence: 99%